FAKTOR PENYEBAB PERKAWINAN ANAK DI KABUPATEN MAJENE MENURUT PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Supriadi, Supriadi; Ansar, Lukman; Ridwan P, Muh. (IAIN BONE, 2024)
This article examines the factors causing the increase in child marriage in Majene Regency, West Sulawesi Province from 2018 to 2022. Apart from aiming to determine the factors causing child marriage, another aim of this research is to determine the impact of child marriage in Majene Regency. The type of research used was qualitative, which was carried out in Majene Regency, West Sulawesi Province. The approach used is theological-normative and juridical-sociological. Data collection techniques through interviews and documentation. Meanwhile, the analysis used is qualitative descriptive analysis. The research results show that: 1). The main factors causing the increase in child marriage in Majene Regency are: (a) School dropout factor. This is due to a lack of knowledge, so it is easily influenced by the environment; (b). Social factors, such as uncontrolled teenage relationships, which result in teenagers' tendency to marry quickly at a young age; (c). Economic factors, economically disadvantaged families encourage child marriage, with the assumption that marrying their children can help the family's economy. 2). The impact of child marriage according to Islamic law and positive law, including: a). reproductive health impacts, potentially threatening the lives of mother and child when giving birth; b). The mental and psychological impact, because child marriage is a burden on children, is something they are not yet able to face mentally. With so many harms resulting from child marriage, according to Islamic law and positive law, child marriage must be prevented and prohibited from occurring.